2017
DOI: 10.14214/sf.6989
|View full text |Cite
|
Sign up to set email alerts
|

Assessing work order information quality in harvesting

Abstract: Highlights• This paper concludes that information quality with regards to accuracy in work order information components pertaining to "Landing -placement and size", "Cleaning understory trees -not conducted and of low standard", are lacking and need to be improved in harvesting. AbstractBeing a logging contractor involves several uncertainties, amongst others, information quality in the work order received from customers. The information quality of work orders is of the utmost importance for logging contactors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
(15 reference statements)
1
6
0
Order By: Relevance
“…For instance, work order information of insufficient quality or that was delivered just before harvesting execution was perceived to drive contractors' adaptability performance but hinder their delivery performance, which instead was driven by the economy factor. This provides more support to earlier studies' identification of timely and reliable work order information as important for contractor profitability and satisfaction as well as for customer satisfaction Gustafsson 2017).…”
Section: Involvementsupporting
confidence: 60%
See 1 more Smart Citation
“…For instance, work order information of insufficient quality or that was delivered just before harvesting execution was perceived to drive contractors' adaptability performance but hinder their delivery performance, which instead was driven by the economy factor. This provides more support to earlier studies' identification of timely and reliable work order information as important for contractor profitability and satisfaction as well as for customer satisfaction Gustafsson 2017).…”
Section: Involvementsupporting
confidence: 60%
“…A contractor can only deliver a requested service if the customer cooperates and provides them with the means to do so. For instance, the accuracy of the provided work order information will enable the contractor to plan and conduct the harvesting operation properly (Gustafsson 2017). In other words, reliable, up-to-date information from the customer will allow the contractor to plan the work well and avoid problematic issues.…”
Section: Involvementmentioning
confidence: 99%
“…Commonly, forestry has a close interdependence of contractors and customers in most of the countries where this activity is important [8,13,15]. Mäkinen [16] applied the Porter's competitive strategies and found that successful contractors of Finland showed a very long-term relationship with a client-up to 20 years-a good use of operational capability, and not too large an operating radius.…”
Section: Introductionmentioning
confidence: 99%
“…According to (Yin, 2003)with using Within Case Analysis and Across Case Analysis it could get the ability to explore the subunits that are located within larger case. The analysis should be easy to understand to fulfil the research purpose, and the benefit of those analyses make deeper understanding of the exploring objects/issues (Gustafsson A., 2017) Research analysis will be conducted in 2 steps, first is to analyse the In-depth Interview using Within Case Analysis and Across Case Analysis regarding to Change Management and Talent Management issues, and second is to prove the desire of SMEs in Growth and Development by Analyse the Questionnaires, so the solution will be more specific about the issues and the SMEs' desires. In addition to interviews, this research also used a Questionnaire.…”
Section: Methodsmentioning
confidence: 99%